The Validity and Reliability of a Smartphone Application for Break-Point Angle Measurement during Nordic Hamstring Exercise - Toshiaki Soga; Shota Yamaguchi; Takayuki Inami; Hiromi Saito; Nadaka Hakariya; Naoto Nakaichi; Sho Shinohara; Kei Akiyama; Norikazu Hirose (North American Sports Medicine Institute, 2023)
# Background A recently developed smartphone application (Nordic Angle) allows the automatic calculation of the break-point angle (BPA) during Nordic hamstring exercise (NHE) without transferring the collected data to a computer. The BPA is the point at which the hamstrings are unable to withstand force. However, the validity of the BPA values obtained by this method has not been examined. # Hypothesis/Purpose This study aimed to evaluate the validity and reliability of the Nordic Angle by comparing the BPA values of the Nordic Angle with those of two-dimensional motion analysis software that can calculate the angles and angular velocities of various joints. # Study Design Cohort assessing Validity and Reliability # Methods The validity of the Nordic Angle BPA data was verified by Spearman's correlation test for consistency with the movement analysis data, and the magnitude of the correlation was indicated by rs. The agreement between these measurements was examined using the Bland-Altman analysis. The reliability of the Nordic Angle and motion analysis was examined using the intraclass correlation coefficient (ICC) (1,k) based on data from repeated trials within a day. # Results Although the spearman correlation between the Nordic angle and the angle determined using motion analysis did not reach statistical significance (p = 0.052), a very large correlation was present (rs = 0.75). The difference between the mean values of the Nordic Angle and motion analysis was 0.4 ± 2.1°, and the limits of agreement ranged from -3.9° to 4.6°. In two BPA measurements, the Nordic Angle showed perfect reliability (ICC = 1.00, p \< 0.001), while motion analysis showed nearly perfect reliability (ICC = 0.97, p \< 0.001). # Conclusion The Nordic Angle, which has both validity and reliability, may be appropriate for field measurement because it allows immediate feedback of BPA and the measurement of many athletes. # Level of evidence 3b